HUBUNGAN KEPATUHAN MENGKONSUMSI TABLET FE DENGAN KADAR HEMOGLOBIN IBU HAMIL DI PUSKESMAS POLANHARJO KLATEN - Sri Wahyuni (Stikes Muhammadiyah Klaten, 2019)
Lack of hemoglobin (Hb) levels of pregnant women is one of the health problems that are prone to occur during pregnancy. An Hb level of less than 11 g / dl indicates that pregnant women suffer from anemia. Anemia control program for pregnant women is to provide 90 Fe tablets during pregnancy with the aim of reducing the anemia rate of pregnant women. The cause of the program's inadequacy was the lack of compliance of pregnant women in consuming Fe tablets. The purpose of this study was to determine the relationship between the compliance of consuming Fe tablets with hemoglobin levels of pregnant women at Polanharjo Klaten Public Health Center. The research method is descriptive with cross sectional approach. The number of samples of the study was 38 pregnant women who had their pregnancychecked at Puskesmas Polanharjo Klaten. Sampling was using purposive sampling technique. The instrument used was a data recapitulation sheet. Data were analyzed by using the chi square test. The results showed that there was a statistically significant relationship between the adherence of consuming Fe tablets and hemoglobin levels of pregnant women (p = 0.000 <0.05).The conclusions in this study indicate that there is a relationship between adherence to consuming Fe tablets with hemoglobin levels of pregnant women.